Physical Stability of Guava Leaves Extract at Different Storage Temperature - Nadya Ambarwati; Amanda Safithri Sinulingga; Ira Purbosari (Indonesian Journal of Pharmaceutical Science and Technology, 2023)
Guava (Psidium guajava L.) has been widely used by Indonesian people as traditional medicine. Guava leaves have been studied and show various pharmacological activities including antidiarrheal, antioxidant, anti-inflammatory, analgesic, antimutagenic, anti-cough, antibacterial, antifungal, antiplaque, suppresses cardiac muscle inotropism, antidiabetic, antihypertensive, hepatoprotective and anticoagulant. In Indonesia, guava leaves have been formulated into several dosage forms. The guava leaves extract, as raw material of traditional medicine, should perform stability during storage period. This study aims to test the physical stability of guava leaves extract, which includes organoleptic, pH, and viscosity at different storage temperature and time susceptibility. Extraction was carried out by maceration method using ethanol 96% as solvent. Extraction is done until a thick extract is obtained. The extract was stored at 8oC (refrigerator temperature), 27oC (room temperature), and 70oC (oven temperature). Physical stability test was performed before storage period and at 1st, 2nd, 3rd week of storage period. Stability test results showed that ethanolic extract of guava leaves was stable at different storage temperatures. The results showed no differences on organoleptic, pH and viscosity test before storage period and at 1st, 2nd, 3rd week of storage period. Key words: Physical stability, Guava leaves, Ethanolic extract